2008
DOI: 10.4049/jimmunol.180.8.5267
|View full text |Cite
|
Sign up to set email alerts
|

CD137 Costimulation of CD8+ T Cells Confers Resistance to Suppression by Virus-Induced Regulatory T Cells

Abstract: Chronic viral infections cause high levels of morbidity and mortality worldwide, making the development of effective therapies a high priority for improving human health. We have used mice infected with Friend virus as a model to study immunotherapeutic approaches to the cure of chronic retroviral infections. In chronic Friend virus infections CD4+ T regulatory (Treg) cells suppress CD8+ T cell effector functions critical for virus clearance. In this study, we demonstrate that immunotherapy with a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 58 publications
2
47
0
Order By: Relevance
“…In addition, the significance of regulatory T cells (Tregs) after anti-CD137 therapy has not been well defined and remains contradictory. Because CD137 is not only expressed on activated effector T cells, but also on CD4 + Foxp3 + Tregs (7), it is unknown whether activation of Tregs through CD137 may drive increased suppressive Treg activity as previously suggested (8).…”
mentioning
confidence: 99%
“…In addition, the significance of regulatory T cells (Tregs) after anti-CD137 therapy has not been well defined and remains contradictory. Because CD137 is not only expressed on activated effector T cells, but also on CD4 + Foxp3 + Tregs (7), it is unknown whether activation of Tregs through CD137 may drive increased suppressive Treg activity as previously suggested (8).…”
mentioning
confidence: 99%
“…CD137 is expressed on a wide variety of cells and anti-CD137 antibodies may have activities other than as simple agonists. 5 The role of CD137 in T reg -cell function is uncertain 6 and it paradoxically ameliorates certain autoimmune diseases. 7,8 More broadly, the immune systems of mice are significantly different from those of humans and several other approaches that have yielded promising data in mice have proved ineffective in humans.…”
Section: Org Frommentioning
confidence: 99%
“…Where this has been done, it was concluded that it is primarily CMV that is responsible for driving these "ageassociated" changes. 6 Therefore, it may be proposed that the increased levels of expression of negative receptors by CD8 cells is in response to the necessity of maintaining these cells in an activated state as effectors responsible for CMV immunosurveillance. An antiproliferative, apoptosis-resistant, CD28 Ϫ , KIR ϩ phenotype (commonly but perhaps erroneously assumed to reflect "senescence") might, in fact, be protective and help to retain essential effector cells because CMV-specific cells constantly exposed to viral antigens might otherwise be stimulated to proliferate until they reached exhaustion and were clonally deleted.…”
mentioning
confidence: 99%
“…10 The effect of CD137 ligation on T regs is not as clearly understood, with conflicting reports showing both stimulation and inhibition of the immunosuppressive functions of these cells. [10][11][12][13][14] Consistent with the costimulatory function of CD137 on T convs , agonistic mAbs against this receptor have been shown to provoke powerful tumor-specific T-cell responses capable of eradicating tumor cells in a variety of murine tumor models including sarcoma, mastocytoma, glioma, colon carcinoma, and myeloma. 3,15 Anti-CD137 mAb has now entered clinical trials for solid tumors (melanoma, renal cell carcinoma, lung cancer, and ovarian cancer) but little is known about its potential therapeutic effect in lymphoma.…”
mentioning
confidence: 99%